2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081208
|View full text |Cite
|
Sign up to set email alerts
|

RSS-based respiratory rate monitoring using periodic Gaussian processes and Kalman filtering

Abstract: Abstract-In this paper, we propose a method for respiratory rate estimation based on the received signal strength of narrowband radio frequency transceivers. We employ a state-space formulation of periodic Gaussian processes to model the observed variations in the signal strength. This is then used in a RaoBlackwellized unscented Kalman filter which exploits the linear substructure of the proposed model and thereby greatly improves computational efficiency. The proposed method is evaluated on measurement data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…This result suggests that for low SNR operating region batch DFT estimator is better whereas for high SNR conditions GP is better in terms of accuracy. It is also to be noted that GP has other advantages, most notably it relaxes data acquisition requirements by not requiring uniform sampling, operating with occasional packet losses, and better fusing the measurements from different communication channels [14]. Therefore, it has an utmost importance to investigate achievable performance, and to select an appropriate estimator.…”
Section: B Evaluation Methodologymentioning
confidence: 99%
“…This result suggests that for low SNR operating region batch DFT estimator is better whereas for high SNR conditions GP is better in terms of accuracy. It is also to be noted that GP has other advantages, most notably it relaxes data acquisition requirements by not requiring uniform sampling, operating with occasional packet losses, and better fusing the measurements from different communication channels [14]. Therefore, it has an utmost importance to investigate achievable performance, and to select an appropriate estimator.…”
Section: B Evaluation Methodologymentioning
confidence: 99%
“…It has also been shown that when one or many Zigbee links are nearby a breathing person, the RSS value of the links change as a person inhales and exhales [17,21,41,42,64]. IEEE 802.15.4 transceivers often make RSS values available to the application.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…It has been shown that when one or many Zigbee links are nearby a breathing person, the RSS value of the links change as a person inhales and exhales [16,21,41,42,64]. IEEE 802.15.4 transceivers often make RSS values available to the application.…”
Section: Measurement Methodsmentioning
confidence: 99%